Dealing with Project Based Learning during COVID-19: Teacher’s Perception Using Educational Video as ELT Media - Nitiasih, Putu Kerti; Budiarta, Luh Gd Rahayu; Adnyayanti, Ni Luh Putu Era; Erinaryani, Ni Nyoman (Language Circle: Journal of Language and Literature, 2021)
This study aimed to determine teachers’ perception toward teaching media in English language learning in the form of educational video using Project-Based Learning elementary school students. This research used case studies as the research method by using qualitative as the research design. Elementary school teachers in Buleleng regency were the object of this research. The content of the video was designed by using Project-based learning as the steps in delivering the material. The data were collected from interviews and a checklist. The analysis result of the research was most teachers preferred to use video as the learning media. The use of the video perceived positive perception by the teacher since video brings effective learning during the pandemic.